Strategically Integrating Risk Management into Intellectual Capital Management - Noor Azlinna, Azizan; Qian, Long Kweh; Wen-Min, Lu; Irene, Wei Kiong Ting (Inderscience Enterprises Ltd., 2015)
This study investigates the effects of intellectual capital and risk management on the efficiency performance of Malaysian general insurers. We employ data envelopment analysis (DEA) to estimate efficiency performance. We run truncated regression with a bootstrapping approach for 16 unique Malaysian general insurers over the period 20082011. We find that intellectual ability and risk management of the sample firms have increased over the period from 2008 to 2011. The truncated regression results show that VAIC and the number of directors on the risk management committee are significantly and positively related to operating efficiency. However, the coefficient on the interaction term between the two variables is significantly negative. As for that related to risk management committee independence, our analysis shows no statistically significant result. This study provides an insight that not only Malaysian Government, but also other countries should strive to promote knowledgebased economy.